Management of Local Internet Content in Nigerian Academic Institutions - Uzuegbu , C.P.; Igwe, K.N. (MiddleBelt Journal of Library and Information Science, 2015)
Nigeria is a country in the western part of Africa with many academic institutions and researchers that are making significant investigations on issues affecting the country and the world at large. However, it is unfortunate that research findings in the form of theses, dissertations, technical reports, and other kinds of grey literature gather dust in these academic institutions. This necessitated the focus of this paper, thus making a case for global visibility of the research efforts. It examined the concept of local internet content and discussed best practices to adopt for the collection, preservation and dissemination of the local content emanating from the academic institutions in the country. This is based on three key players – academic institutions, information and communication technology (ICT) infrastructure, and personnel. It concluded that, as a matter of necessity, Nigeria should put necessary measures in place for showcasing its local content on the web for the furtherance of knowledge and overall development in our global knowledge society.